Selection and validation of appropriate reference genes for real-time quantitative PCR analysis in Momordica charantia. (August 2019) - Wang, Zhenglong; Xu, Jiyang; Liu, Yihan; Chen, Jiyu; Lin, Hanfeng; Huang, Yanli; Bian, Xiaohong; Zhao, Yucheng
Abstract: Real time quantitative reverse transcription PCR (RT-qPCR) has been attracting more attention for its high sensitivity in gene expression analysis. Given the widely use of RT-qPCR in normalization, it is playing a pivotal role for seeking suitable reference genes in different species. In current work, 12 candidate reference genes including Actin 2 ( ACT2 ), Cyclophilin 2 ( CYP2 ), Glyceraldehyde-3-phosphate dehydrogenase C2 ( GAPC2 ), Elongation factor 1-α ( EF1-α ), Nuclear cap binding protein 20 ( NCBP20 ), Serine/threonine-protein phosphatase PP2A ( PP2A ), Polypyrimidine tract-binding protein 1 ( PTBP1 ), SAND family protein ( SNAD ), TIP41-like protein ( TIP41 ), Tubulin beta-6 ( TUB6 ), Ubiquitin-conjugating enzyme 9 ( UBC9 ) and Glyceraldehyde-3-phosphatedehydrogenase ( GAPDH ) were screened from the transcriptome datasets of M. charantia . Afterwards, GeNorm, NormFinder and BestKeeper algorithms were applied to assess the expression stability of these 12 genes under different abiotic stresses including drought, cold, high-salt, hormone, UV, oxidative and metal stress. The results indicated that 12 selected genes exhibited various stability across the samples under different external stress conditions, but TIP41, PTBP1 and PP2A presented high stability among all the reference genes. To validate the suitability of the identified reference genes, the results of hormone subset were compared with RNA sequencing (RNA-seq) data, and the relative abundance of Ascorbate peroxidase 1（ APX1 ）was used to confirm the reliability of the results. This work assesses the stability of reference genes in M. charantia under different abiotic stress conditions, which will be beneficent for accurate normalization of target genes in M. charantia . Graphical abstract: Image 1 Highlights: 12 candidate reference genes were screened from the transcriptome datasets of M. charantia . Stability of 12 candidate reference genes of Momordica charantia were assessed . TIP41, PTBP1 and PP2A are the most reliable reference genes for the RT-qPCR analysis.